2020
DOI: 10.1371/journal.pone.0234812
|View full text |Cite
|
Sign up to set email alerts
|

Age and cohort rise in diabetes prevalence among older Australian women: Case ascertainment using survey and healthcare administrative data

Abstract: Background Due to the absence and or costliness of biological measures such as glycated haemoglobin, diabetes case ascertainment and prevalence studies are usually conducted using surveys or routine health service use databases. However, the use of each of these sources is associated with its limitations potentially impacting the quality of the case ascertainment and prevalence estimation. This study aimed at ascertaining diabetes cases and estimating prevalence among mid-and older-age women through simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…Importantly, when we compared women between cohorts at roughly the same age, we found that women from the 1989–95 cohort had higher prevalence of diabetes and cardiac disease (which was largely driven by hypertension), with the prevalence of both conditions continuously increasing with age across the observation period. A similar age-wise trend for diabetes has been demonstrated with the two oldest cohorts of the ALSWH [ 17 ]. While some of the increase in prevalence at earlier ages for these conditions may be attributed to improved diagnostic techniques and early detection, findings from the U.S. suggest that even among adults with regular primary care access, those aged 18–39 were unlikely to receive a hypertension diagnosis compared to adults at least 40 years old despite meeting criteria for diagnosis [ 56 ].…”
Section: Discussionsupporting
confidence: 71%
“…Importantly, when we compared women between cohorts at roughly the same age, we found that women from the 1989–95 cohort had higher prevalence of diabetes and cardiac disease (which was largely driven by hypertension), with the prevalence of both conditions continuously increasing with age across the observation period. A similar age-wise trend for diabetes has been demonstrated with the two oldest cohorts of the ALSWH [ 17 ]. While some of the increase in prevalence at earlier ages for these conditions may be attributed to improved diagnostic techniques and early detection, findings from the U.S. suggest that even among adults with regular primary care access, those aged 18–39 were unlikely to receive a hypertension diagnosis compared to adults at least 40 years old despite meeting criteria for diagnosis [ 56 ].…”
Section: Discussionsupporting
confidence: 71%
“…Among critically ill patients in India, 13.9% of the 1283 admissions in ICU over 4 years were established cases of diabetes, with 5.0% diagnosed as diabetes after admission. Past studies [ 17 , 31 ] have also reported significant interaction between pre-existing hyperglycaemia and the association between acute glycaemia and mortality among people with diabetes in ICU [ 17 ]. In-hospital control of glucose in people with diabetes receiving ICU care is associated with a reduced length of hospital stay and lower mortality rate [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…People were coded by their place of residence rather than admission hospital [16]. Since acute hospital admissions in Australia mainly occur in public hospitals, for this study, only public hospital APDC data of episodes of care was used, which has previously been validated in people with diabetes, and other populations [17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…For this study, only public hospital APDC data of episodes of care were used [ 18 ]. The APDC dataset has been previously validated in people with and without diabetes [ 19 21 ]. For instance, when APDC was used as a standard for validating self-reported diabetes status of people in the 45 and up study, the authors were able to identify 48.3% more people with diabetes whose status were not previously reported in their dataset [ 22 ].…”
Section: Methodsmentioning
confidence: 99%